Phytochemical profile of Paulownia tomentosa (Thunb). Steud - Schneiderová, Kristýna; Šmejkal, Karel (Phytochemistry reviews, 2015)
Paulownia tomentosa, a member of the plant family Paulowniaceae and a rich source of biologically active secondary metabolites, is traditionally used in Chinese herbal medicine. Flavonoids, lignans, phenolic glycosides, quinones, terpenoids, glycerides, phenolic acids, and miscellaneous other compounds have been isolated from different parts of P. tomentosa plant. Recent interest in this species has focused on isolating and identifying of prenylated flavonoids, that exhibit potent antioxidant, antibacterial, and antiphlogistic activities and inhibit severe acute respiratory syndrome coronavirus papain-like protease. They show cytotoxic activity against various human cancer cell lines and inhibit the effects of human cholinesterase, butyrylcholinesterase, and bacterial neuraminidases. Most of the compounds considered here have never been isolated from any other species of plant. This review summarizes the information about the isolated compounds that are active, their bioactivities, and the structure-activity relationships that have been worked out for them.
Keywords: Paulownia tomentosa; Phenolic glycosides; Paulowniaceae; Flavonoid; Lignan; Bignonia tomentosa